BaCo0.4Fe0.4Zr0.2O3-δ Cathode Materials for Protonic Ceramic Fuel Cells. (10th July 2019) - Saqib, Muhammad; Lee, John In; Park, Jun-Young
Abstract : In order to investigate a high-performance and durable cathode material for protonic ceramic fuel cells (PCFCs), we prepare BaCo0.4 Fe0.4 Zr0.2 O3-δ (BCFZ) materials and analyze systematically using X-ray diffraction and scanning electron microscopy to obtain a single-phase perovskite material. Chemical compatibility of BCFZ with BaCe0.7 Zr0.1 Y0.2-x Ybx O3-δ (BCZYYb) at high temperature (1000 °C for 8 h) exhibited no secondary-phase formation, indicating that they have good chemical compatibility with each other. We use electrochemical impedance spectroscopy to evaluate the electrochemical performance using a BCZYYb symmetrical cell configuration. BCFZ at 600 °C in humidified (3% H2 O) air shows 1.62 Ω·cm 2 polarization resistance, comparable to Ba0.5 Sr0.5 Co0.8 Fe0.2 O3-δ (BSCF), which showed 1.77 Ω·cm 2 . This result demonstrates that BCFZ has an excellent oxygen-reduction reaction for PCFCs, especially at intermediate temperatures. The desired electrochemical activity for BCFZ has inspired us to explore new dopants that could further improve electrocatalytic activity for ORR at low temperatures.